The effect of an active transcutaneous bone conduction device on spatial release from masking. (30th April 2020) - Rigato, Cristina; Reinfeldt, Sabine; Asp, Filip
Abstract: Objective: The aim was to quantify the effect of the experimental active transcutaneous Bone Conduction Implant (BCI) on spatial release from masking (SRM) in subjects with bilateral or unilateral conductive and mixed hearing loss. Design: Measurements were performed in a sound booth with five loudspeakers at 0°, +/−30° and +/−150° azimuth. Target speech was presented frontally, and interfering speech from either the front (co-located) or surrounding (separated) loudspeakers. SRM was calculated as the difference between the separated and the co-located speech recognition threshold (SRT). Study Sample: Twelve patients (aged 22–76 years) unilaterally implanted with the BCI were included. Results: A positive SRM, reflecting a benefit of spatially separating interferers from target speech, existed for all subjects in unaided condition, and for nine subjects (75%) in aided condition. Aided SRM was lower compared to unaided in nine of the subjects. There was no difference in SRM between patients with bilateral and unilateral hearing loss. In aided situation, SRT improved only for patients with bilateral hearing loss. Conclusions: The BCI fitted unilaterally in patients with bilateral or unilateral conductive/mixed hearing loss seems to reduce SRM. However, data indicates that SRT is improved or maintained for patients with bilateral and unilateral hearing loss, respectively.